1980
DOI: 10.1073/pnas.77.7.4345
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic patterns of thyrotropin-releasing hormone-like material in rat hypothalamus, pancreas, and retina: selective effect of light deprivation.

Abstract: ABSTRACr Recent observations have shown the presence of thyrotropin-releasing hormone-like material (TRH-LM) in rat pancreatic islets and in retina. Its immunological and biological properties are identical to those of synthetic thyrotropin-releasing hormone (thyroliberin) This communication deals with the ontogenesis of TRH-LM in rat pancreas and retina as compared to that of rat hypothalamus. Effects of sex and exposure to constant dark were also studied. Results show that asynchronous changes in the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…This work was presented in part at the 63rd Annual Meeting of the Endocrine Society, [17][18][19] June 1981, Cincinnati, Ohio.…”
mentioning
confidence: 99%
“…This work was presented in part at the 63rd Annual Meeting of the Endocrine Society, [17][18][19] June 1981, Cincinnati, Ohio.…”
mentioning
confidence: 99%
“…Its pattern of expression is tightly controlled in a temporal and cell-type-specific manner. Indeed, in the pancreas, TRH is found at high levels specifically in insulin-expressing cells at around the time of birth, the TRH levels decreasing very rapidly during the first days of postnatal life (Martino et al 1980, Leduque et al 1987, Scharfmann et al 1988. Such data were mainly obtained at the protein level.…”
Section: Discussionmentioning
confidence: 88%
“…Its expression is also tightly regulated temporally. Indeed, a large number of studies have demonstrated that the levels of TRH are high in pancreatic beta cells during the neonatal period (Martino et al 1980, Aratan-Spire et al 1984 and decrease rapidly, when postnatal development progresses (Martino et al 1980, Aratan-Spire et al 1984, Scharfmann et al 1988. To the best of our knowledge, the prenatal pattern of pancreatic TRH expression remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoreactive TRH was later detected in the rat pancreas (3,4) where its concentration, as well as the levels of its messenger RNA, are highest during the neonatal period (5)(6)(7)(8). Within the pancreas, TRH is localized in the insulin-producing B-cells of the islets of Langerhans (9)(10)(11).…”
Section: Introductionmentioning
confidence: 98%